The effects of wind power on electricity markets - Hu, Xiao,Jaraitė, Jūratė,Kažukauskas, Andrius (Department of Economics, Umeå University, 2020)
We investigate the process of electricity price formation in the Swedish intraday market, given a large share of wind power in the Swedish electricity system. According to Karanfil and Li’s (2017) approach, if the intraday market is efficient and liquid, with large shares of intermittent electricity in the entire electricity system, the intraday price should send signals based on scarcity pricing for balancing power. Based on this theory, we analyze the Swedish electricity market data for the period 2015–2018 and find that the Swedish intraday market, despite its small trading volumes, is functioning properly. In particular, our results show that intraday price premia respond in an expected way to wind power forecast errors and other imbalances resulting from either supply or demand sides of the electricity market. The results of wind power forecast errors hold for central and southern Sweden, but not for northern Sweden where the share of wind power production is still very small. In addition, we find no effect of unplanned nuclear power plant outages on intraday price premia
10.2139/ssrn.3610800
Keywords: Graue Literatur; day-ahead market; electricity; forecast errors; intraday market; Sweden; wind power